Modeling the Structural Relationships of Adolescent Self-Control within the Family Environment: The Mediating Role of Rumination and the Influence of Parenting Styles, Family Emotional Support, and Cognitive Flexibility - Issazadegan, Ali; Chitsaz, Mahdi (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aims to examine the structural model of adolescent self-control within the family context, focusing on the contributions of parenting styles, family emotional support, and cognitive flexibility, with rumination as a mediating factor. Methods and Materials: Using a correlational design, this study targeted a population of adolescents aged 12–18 years attending urban schools in Azarshahr, Iran, in 2023. A sample of 385 adolescents was selected via multi-stage cluster sampling. Data were collected using validated instruments: the Parenting Styles Questionnaire (Darling & Toyokawa, 1997), Family Emotional Support Scale (Pierce, Sarason, & Sarason, 1991), Cognitive Flexibility Scale (Dennis & Vander Wal, 2010), and Rumination Response Scale (Nolen-Hoeksema & Morrow, 1991). Data analysis was conducted using SmartPLS software, applying structural equation modeling (SEM) to test the hypothesized model. Findings: The findings revealed significant direct effects of parenting styles, family emotional support, and cognitive flexibility on adolescent self-control (p < .05, effect size = .2). Rumination significantly mediated the relationships between these factors and self-control, underscoring its role within this dynamic. Conclusion: The results indicate that fostering positive parenting styles, supportive family environments, and flexible cognitive abilities can enhance adolescent self-control, with reduced rumination serving as a beneficial mediator. This model highlights the potential of family-centered approaches in promoting adolescent self-regulation.